Functionalized Copper Phthalocyanine and Zinc Phthalocyanine as a Coating Layer on the Sensitivity of QCM-Based VOCs Sensor - Masruroh Masruroh; Rachmat Triandi Tjahjanto; Gancang Saroja; Dionysius J. D. H. Santjojo (Department of Physics, Sebelas Maret University, 2023)
The sensitivity of a QCM-based VOCs sensor with two kinds of a metal phthalocyanine, i.e., copper phthalocyanine (CuPc) and zinc phthalocyanine (ZnPc) was examined for various VOCs. The sensitivity of the two metal phthalocyanine was determined by the compatibility of the overlapped metal orbitals (Cu(II) dan Zn(II)) and the corresponding VOCs. The CuPc and the ZnPc layer were deposited on the quartz crystal oscillator by a vacuum evaporation method. The frequency shift and the sensitivity of the sensors with the two functional layers were tested using 5 VOCs: formaldehyde, propanol, ethanol, toluene, and ketone. The CuPc sensor showed the highest sensitivity to formaldehyde. On the other hand, the ZnPc was highly sensitive to ethanol.